1995
DOI: 10.1089/neu.1995.12.169
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Parasagittal Controlled Cortical Impact in the Mouse: Cognitive and Histopathologic Effects

Abstract: Controlled cortical impact (CCI), using a pneumatically driven impactor to produce traumatic brain injury, has been characterized previously in both the ferret and in the rat. In the present study, we applied this technique to establish and characterize the CCI model of brain injury in another species, the mouse, evaluating cognitive and histopathologic outcome. In anesthetized (sodium pentobarbital, 65 mg/kg) male C57BL mice, we performed sham treatment (no injury, n = 12) or CCI injury (n = 12) at a velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
316
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 393 publications
(336 citation statements)
references
References 33 publications
(39 reference statements)
16
316
0
4
Order By: Relevance
“…Previous studies using CCI in mice reported selective vulnerability to neuronal death in CA3 and the hilar regions, as well as dentate gyrus (Hall et al, 2005;Saatman et al, 2006;Smith et al, 1995). Using a depth of CCI set at 0.6 mm, we also observed robust cellular injury using H&E staining in ipsilateral cortex, CA3 and hilus, and dentate gyrus.…”
Section: Spatiotemporal Distribution Of Cell Death After Controlled Csupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies using CCI in mice reported selective vulnerability to neuronal death in CA3 and the hilar regions, as well as dentate gyrus (Hall et al, 2005;Saatman et al, 2006;Smith et al, 1995). Using a depth of CCI set at 0.6 mm, we also observed robust cellular injury using H&E staining in ipsilateral cortex, CA3 and hilus, and dentate gyrus.…”
Section: Spatiotemporal Distribution Of Cell Death After Controlled Csupporting
confidence: 58%
“…Propidium iodide labeling appeared in distinct populations of traumatically injured brain cells in regions known to be vulnerable to traumatic cell death (Clark et al, 1997;Colicos et al, 1996;Hannay et al, 1999;Smith et al, 1995), including cortex, CA3, the hilar region, and dentate gyrus, with relative sparing of CA1.…”
Section: Propidium Iodide Label Cells In Injured Brain Regions Selectmentioning
confidence: 99%
“…El modelo de CCI determina fundamentalmente un área de necrosis focal en la corteza, rodeada de un área edematosa que va creciendo progresivamente, reproduciendo todo el espectro de lesiones cerebrales contusivas en humanos 32,68 . Sin embargo, la alteración neuropatológica es realmente más difusa e incluye además del daño cortical, pérdida de células en hipocampo, giro dentado y tálamo ipsilateral que se puede extender al hemisferio contralateral cuando la intensidad del impacto es mayor 43,48,98 . Otras alteraciones anatomopatológicas asociadas son la lesión axonal a nivel de la sustancia blanca subcortical, cápsula interna, núcleos talámicos y tronco cerebral.…”
Section: El Modelo De Impacto Cortical Controlado -Controlled Corticunclassified
“…CCI injury is caused by the rapid depression of the dura by a flat-faced, cylindrical piston. Earlier models employed a pneumatically-driven impactor [11][12][13], while a more recently engineered device is electromagneticallyregulated, and reportedly results in better control of load velocity, impact depth, and reproducibility [14]. The Impact One™ Stereotaxic Impactor for CCI from myNeuroLab, for example, uses an electromagnetically-driven impactor.…”
Section: B 4 B the Controlled Cortical Impact Modelmentioning
confidence: 99%